Leaf Disease Detection using Image Processing Technique- A Survey - Kumar, Ajay (International Journal of Computer Sciences and Engineering, 2025)
This paper contains the review of different image processing techniques to detect various leaf diseases using machine learning. Now a day’s image processing technique is becoming a key technique for diagnosing the various features of the leaves. The diseases can touch part or area of the leaf. This paper mainly focuses detection of various leaf diseases and to classify them. The detection of leaf disease is mostly based on type of family leafs and same is approved by segmentation and classification. There are so many classification techniques such as Decision tree classifier, k-Nearest Neighbour classifier , kmeans Classifier, Probabilistic Neural Network, Genetic Algorithm, Support Vector Machine, and Principal Component Analysis, Artificial neural network, Fuzzy logic. Assortment of classification method is always a difficult job because the quality of result can differ for dissimilar input data. This paper provides an overview of diverse classification techniques used for leaf disease classification [1].